Struktur Organisasi dan Model Kepemimpinan di Madrasah: Analisis Manajemen Pendidikan di MTsN 1 Takengon - Andriani, Tiffani; Musdar, Musdar (PAI Fakultas Tarbiyah & Ilmu Keguruan UIN SUNA Lhokseumawe, 2025)
This study aims to analyse the relationship between organizational structure and the leadership style of the principal at MTsN 1 Takengon in managing educational administration. A qualitative approach with a case study design was employed to explore the phenomenon in depth. Data were collected through observations, semi-structured interviews, and document analysis, and subsequently analysed using Miles & Huberman’s interactive model. The findings reveal that the organizational structure implemented is relatively effective in distributing tasks, although overlaps in authority remain within several work units. In terms of leadership, the principal adopts a combination of transformational, participative, and transactional styles, which positively influence teachers’ and staff’s motivation, creativity, and discipline. The synergy between organizational structure and leadership is proven to be a crucial factor in improving the quality of school management. The implication of this study highlights the need to strengthen interdepartmental coordination and to develop a more consistent and adaptive leadership style, enabling the madrasah to better respond to educational challenges.